The Effect of Older Siblings on Language Development as a Function of Age Difference and Sex. (September 2019) - Havron, Naomi; Ramus, Franck; Heude, Barbara; Forhan, Anne; Cristia, Alejandrina; Peyre, Hugo; ,
The number of older siblings a child has is negatively correlated with the child's verbal skills, perhaps because of competition for parents' attention. In the current study, we examined the role of siblings' sex and age gap as moderating factors, reasoning that they affect older siblings' tendency to compensate for reduced parental attention. We hypothesized that children with an older sister have better language abilities than children with an older brother, especially when there is a large age gap between the two siblings. We reanalyzed data from the EDEN cohort ( N = 1, 154) and found that children with an older sister had better language skills than those with an older brother. Contrary to predictions, results showed that the age gap between siblings was not associated with language skills and did not interact with sex. Results suggest that the negative effect of older siblings on language development may be entirely due to the role of older brothers. Our findings invite further research on the mechanisms involved in this effect.